Antimicrobial resistance trends in Escherichia coli in South African Poultry: 2009-2015 - (:unkn) unknown (My University, 2019)
Prolonged and widespread in-feed use of antimicrobials as either growth promoters or to treat bacterial infections in commercial poultry production contributed to the emergence of resistant bacterial strains globally. A total of 3544 avian pathogenic Escherichia coli strains isolated from commercial broilers in South Africa between 2009 and 2015 were tested for susceptibility against eight classes of antimicrobials. Time series analyses were conducted to assess seasonal and general trends in antibiotic resistance. Seasonal trends were seen in the tetracyclines, with peaks of resistance in the winter months when respiratory diseases are at their worst. Resistance to quinolones peaked in 2012 after which there was an overall decreasing trend in resistance. Colistin resistance increased gradually from 2009 with a drastic rise to 12.08% in 2015, but its use in feed was stopped in 2016. Florfenicol also showed a sharp increase in resistance from 2.36% in 2009 to 6.63% in 2015. Resistance to trimethoprim-sulphadiazine decreased sharply by the end of 2015, as did spectinomycin and fosfomycin and amoxicillin. The overall prevalence of multidrug resistance (MDR) was 80.6 (95% confidence interval, 0.743-0.819), but the years 2013, 2014, and 2015 showed a significantly lower level of MDR compared with 2009. This study is the first detailed analysis of antimicrobial resistance in poultry production in the country, and constant monitoring of resistance data should be continued to aid in the judicious use of antimicrobial compounds.
Keywords: African Research